Appendectomy for Vague Symptoms and Equivocal Physical Findings on Physical Exam and Computed Tomography. Issue 4 (April 2022) - Flatley, Meaghan; Sokol, Kyle K.; Balent, Eric M.; Placek, Sara B.; Ritenour, Joshua S.; Sparkman, Brian K.
Background: Appendicitis is a common condition affecting 7-8% of the general population. With the improvement of noninvasive imaging, the diagnostic approach and treatment algorithm for patients with clear signs and symptoms suggestive of acute appendicitis are well agreed-upon. However, patients without pathognomonic signs and symptoms, but with equivocal imaging pose a diagnostic dilemma. These patients may still have acute appendicitis and could potentially benefit from laparoscopic appendectomy. This may be especially true in the subset of patients with appendicoliths. Methods: Our case series exams a group of patients with atypical symptoms who eventually underwent appendectomy and were followed after surgery for at least a month. This case series consists of eight patients with abdominal pain accompanied by a variety of other signs and symptoms in addition to laboratory results and imagining characteristics which were nondiagnostic. These patients had initial Alvarado scores ranging from 0-6. Results: All of these patients were subsequently taken to the operating room for diagnostic laparoscopy and laparoscopic appendectomy. Of these patients, six were known to have appendicoliths based on computed tomography obtained during initial diagnostic workup. Conclusions: All patients underwent a diagnostic laparoscopy and appendectomy. Four had appendicitis and four also had resolution of their symptoms. There exist atypical presentations of appendiceal disease. Patients with abdominal pain/tenderness, even without diagnostic laboratory results or imaging characteristics, may benefit from laparoscopic appendectomy.